A Systematic Review of Negative Work Behavior: Toward an Integrated Definition - Verschuren, Cokkie M.; Tims, Maria; de Lange, Annet H. (Frontiers in Psychology, 2021)
The goal of this systematic review was to identify overlapping and unique aspects of negative work behaviors’ (NWB) operationalizations to specify a new integrative definition of NWB. More specifically, we examined 1) how many operationalizations and conceptualizations of NWB can be identified, 2) whether these operationalizations can be categorized into specific focus areas (i.e., physical, psychological, material, social, actor types and roles), 3) what the meaningful overlap was in these operationalizations, 4) whether the operationalizations tapped unique and meaningful elements (i.e., positive labels, dynamic process), and 5) how the overlapping and unique elements of the operationalizations could be integrated into a new theory-based research model for NWB for future research. In the literature search based on the Prisma framework, Pubmed, PsycINFO, and Google Scholar, we identified k=462 studies that met the inclusion criteria of our review. Results of these studies revealed 16 frequent studied NWB labels (e.g., bullying, aggression). Many of these could be categorized in the same way, namely in terms of type of behavior, type of harm and type of actor involved in the NWB. In our new definition of NWB, we integrated the content of the overlap and meaningful unique elements of the 16 labels.